Chameleon-MAC: Adaptive and Self-⋆ Algorithms for Media Access Control in Mobile Ad Hoc Networks - Leone, Pierre; Papatriantafilou, Marina; Schiller, Elad M.; Zhu, Gongxi (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2010)
In mobile ad hoc networks (MANETs) mobile nodes do not have access to a fixed network infrastructure and they set up a communication network by themselves. MANETs require implementation of a wireless Medium Access Control (MAC) layer. Existing MAC algorithms that consider no mobility, solve the problem of eventually guaranteeing every node with a share of the communications bandwidth. In the context of MANETs, we ask: Is there an efficient MAC algorithm when mobility is considered? MANETs are subject to transient faults, from which self-stabilizing systems can recover. The self-stabilization design criteria, and related concepts of self-⋆, liberate the application designer from dealing with low-level complications, and provide an important level of abstraction. Whereas stabilization criteria are important for the development of autonomous systems, adaptation is imperative for coping with a variable environment. Adapting to a variable environment requires dealing with a wide range of practical issues, such as relocation of mobile nodes and changes to the motion patterns. This work proposes the design and proof of concept implementation of an adapted MAC algorithm named Chameleon-MAC, which is based on a self-stabilizing algorithm by Leone et al., and uses self-⋆ methods in order to further adapt its behavior according to the mobility characteristics of the environment. Moreover, we give an extensive treatment of the aspects and parameters that can bring the algorithm into the practical realm and we demonstrate documented behavior on real network studies (MICAz 2.4 GHz motes) as well as using simulation (TOSSIM [32]), showing improved overhead and fault-recovery periods than existing algorithms. We expect that these advantages, besides the contribution in the algorithmic front of research, can enable quicker adoption by practitioners and faster deployment.